2019
DOI: 10.1001/jamanetworkopen.2019.9951
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Deep Surgical Site Infection After Repair of Periarticular Knee Fractures

Abstract: This systematic review and meta-analysis examines the prevalence of deep surgical site infections after surgical repair of periarticular knee fractures, and the prevalence of septic arthritis, common microorganisms in infection cultures, and covariates associated with surgical site infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
4
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 130 publications
(557 reference statements)
0
34
4
2
Order By: Relevance
“…weight, smoking, previous illnesses) and fracture-or operation-dependent factors (e.g. fracture morphology, compartment syndrome, polytrauma) [16][17][18]. Furthermore, the exact mechanism on how fracturoscopy has a positive effect on reducing SSI remains unclear; possible factors may include low operative complication rates such as lower blood loss and smaller operative approach with less soft tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…weight, smoking, previous illnesses) and fracture-or operation-dependent factors (e.g. fracture morphology, compartment syndrome, polytrauma) [16][17][18]. Furthermore, the exact mechanism on how fracturoscopy has a positive effect on reducing SSI remains unclear; possible factors may include low operative complication rates such as lower blood loss and smaller operative approach with less soft tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐related risk factors, such as age, DM, obesity, tobacco use, alcohol use, and immunosuppression can play an important role in the development of SSI 43 . Norris et al 56 completed a systematic review on SSI incidence after knee fracture repair and noted that patients with a history of smoking, diabetes, or compartment syndrome are at greater risk for development of an SSI. This may be related to impaired microvascular blood flow and inadequate ability to transport antibiotics or necessary white blood cells to fight an infection.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the reported incidence of CS following tibial plateau fracture ranges from 0.7 to 12% [26,29,[50][51][52][53]. Although a somewhat controversial topic with conflicting findings in the literature, acute compartment syndrome requiring fasciotomy has been reported in some studies to significantly increase the rate of non-unions [27] and infections [27,[54][55][56]. On the other hand, Ruffalo et al [57] found no increase in the association of nonunion and infection.…”
Section: Compartment Syndromementioning
confidence: 99%
“…A 2019 meta-analysis including 7925 patients found the incidence of superficial and deep surgical site infections after tibial plateau fracture repairs to be 4.2% and 5.9%, [54][55][56]125], compartment syndrome [27,[54][55][56], smoking [55,56,125], alcohol intake [126], definitive external fixation [56,94] and intraoperative duration approaching 3 h [54,56,125]. A recent article found a strong correlation between a significantly higher peak of C-reactive protein (CRP) >100 μg/ mL on postoperative day 3 and the development of surgical site infections in tibial plateau patients [127].…”
Section: Surgical Site Infectionmentioning
confidence: 99%